One-step hydrothermal synthesis of bismuth sulfide aerogel for efficient iodine capture - Wang, Renren; Xiao, Hao; Tan, Yi; Chen, Luo; Zhou, Yuhang; Xie, Runfeng; Tan, Chuan; Yang, Yifei; Liu, Cheng; Wang, Hengyang; Yang, Junxiao; Duan, Tao; et al. (Frontiers in Environmental Science, 2025)
The efficient capture of radioactive iodine is critical for nuclear safety due to its high mobility and toxicity. Bismuth sulfide (Bi2S3) aerogel, synthesized via a one-step hydrothermal method, demonstrates exceptional iodine adsorption performance. Characterization by scanning electron microscopy (SEM) and BET confirmed the material’s porous structure, which facilitated iodine uptake. Batch experiments revealed a high adsorption capacity of 1,204 mg/g, with kinetics and isotherms well described by the pseudo-second-order model and Freundlich isotherm, respectively, indicating that the adsorption process is dominated by chemisorption. The adsorption mechanism involves iodine phase transfer and subsequent formation of stable BiI3 phases, ensuring long-term immobilization. The Bi2S3 aerogel demonstrates superior chemical and thermal stability, high capture efficiency, and cost-effectiveness, further highlighting its practical potential for nuclear waste management. This work advances the design of bismuth-based adsorbents by combining high capacity, stability, and scalable synthesis, thereby offering a sustainable solution for radioactive iodine capture.